Problem-Driven Governance and Political Economy Analysis : Good Practice Framework - Fritz, Verena; Kaiser, Kai; Levy, Brian (World Bank, Washington, DC, 2014)
Politics and the political economy matter for whether and how reforms happen in developing as well as in developed countries. The World Bank as an institution and its individual country and task teams has been grappling with this issue for many years. The good practice framework described here is an attempt to summarize relevant analytic tools and approaches, to indicate how it can be used (more) systematically, and to make key lessons readily available. It also seeks to set out how such tools can be used in a way that is problem driven, that is, focused on specific issues and challenges rather than on developing broad overviews, in order to generate operationally relevant findings and implications. Integrating governance and political economy (GPE) analysis more systematically into Bank operational work is important to enhance development effectiveness, to better address risks, and to respond to client demands for approaches that are tailored to specific situations. The objective of this framework is to systematize approaches to GPE analysis and to provide orientation for teams that are considering undertaking it. The framework especially draws on the experience with a number of pilot studies undertaken in FY2008 and FY2009, as well as on earlier studies. Analysis focused on a variety of sectors- electricity, transport, and telecommunications, water, and public sector reforms and on thematic challenges, especially the management of natural resource wealth. The framework is therefore tailored to the context of Bank operations and strategy development (such as country assistance strategies) designed to show how GPE analysis can be used to inform and shape them to support more effective development. The framework is divided into six parts: part one discusses the overall rationale of this framework and sets out the key foundations. Part two discusses how PGPE analysis can be used to inform and shape Bank strategies and operations, and offers options for translating the analysis into action more broadly. Part three sets out the various levels of analysis that may be undertaken, from an overall country focus, to a sector or thematic focus, to a GPE analysis that is undertaken to inform specific projects or policy decisions. Part four addresses the issue of evidencing a GPE analysis, a key challenge in producing high-quality work. Part five addresses process issues that arise when undertaking GPE-type analysis. Finally, part six gives conclusion and looking forward.